The long way home [large type] - Pilcher, Robin (Center Point Pub., 2010)
When Claire Barclay receives news that her beloved stepfather has had a stroke, Claire and her husband, Art, leave New York and fly back to Scotland to care for him during the summer. When their visit makes clear that Leo is no longer capable of living on his own but determined to stay in his beloved old house, they offer to purchase the place from Leo and build him a cottage on the property. But Claire's old flame Jonas Fairweather (who has become Leo's caretaker and trusted confidant) has other plans.